Influence of physiological maturity on germinability in pearl millet (Pennisetum glaucum) - SULTANA, ADIB; MENGESHA, M H; JANA, M K; RAO, S APPA (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during the rainy season 1988 to srody tl!e effect of physioiogicai maturity on germination of pearl millet [Pennisetum glaucum (L.) R Br. emend. Stuntz]. When pearl millet seeds were harvested at different stages of maturity at 1-week intervals following stigma emergence, there was a gradual decrease in the water content of the developing seed from 87 to 11 %. This was accompanied by an increase in the dcy-matter accumulation from 1.6 to 10.6 g/l 000 grain with a corresponding increase in the seed germination. Physiological maturity was attained at 11 % moisture content, which was 35-42 days after stigma emergence. This may be used as the harvest date for this crop. Germinable seeds may be collected much earlier than the time of maximum dry-weight accumulation.